An Active-Only Temperature-Insensitive Current-Mode Biquad Filter Based on Differentiator Structures Employing CCCCTAs - Supawat Lawanwisut; Montree Siripruchyanun; Winai Jaikla (My University, 2013)
This article presents an active-only current-mode universal biquad filter performing three standard functions: low-pass, high-pass and band-pass function, which can be readily modified to achieve the rest functions (band-stop and all-pass). The circuit principle is based on active-only circuit designed by using differentiators which are constructed from current controlled current conveyor transconductance amplifier (CCCCTA) cooperating with an internally frequency compensated operational amplifier (OA). The features of the circuit are that: the pole frequency and quality factor can be independently tuned via the input bias currents and it is ideally temperature-insensitive, its circuit description is very simple, consisting of 3 CCCCTAs and 2 operational amplifiers, and the proposed circuit is very appropriate for further developing into integrated circuit architecture. The PSpice simulation results are shown. The given results agree well with the theoretical anticipation.
Keywords: Digital biquad filter; Differentiator; Current conveyor; Current-feedback operational amplifier; Operational transconductance amplifier; Analog and Mixed-Signal Circuit Design